Depression and other correlates of adult Attention Deficit Hyperactivity Disorder (ADHD) symptoms among Hungarian university students - V. Müller; B. Pikó (European Psychiatry, 2022)
Introduction Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity, and/or impulsivity. It is one of the most common disabilities in college populations and comorbidity with depression is frequently reported.